Հանքալեռնային տարածքներում աճեցված բանջարեղենում պոտենցիալ թունավոր տարրերի ռիսկի գնահատում 268 - Պիպոյան, Դավիթ; Արշակյան, Եպրաքսյա; Կարեյան, Տարոն; Բեգլարյան, Մելինե (ՀԱԱՀ հիմնադրամ)
This research assesses the health risks associated with exposure to toxic (Pb, Cd, As, Hg) and potentially toxic elements (Mo, Cu) through the consumption of vegetables (potato, carrot, bean, fennel, pumpkin) grown near mining areas. Using the Margin of Exposure (MOE) method for risk assessment, this study provides a more accurate evaluation compared to previous studies that relied on the Target Hazard Quotient (THQ) calculation method. The results of the current research indicated concerning risk values (MOE<10) for lead, molybdenum and copper associated with the consumption of the studied vegetables, and for arsenic in the case of potato and fennel consumption among the adult resident population in the studied area. By comparing the results obtained using the target hazard ratio (THQ) and the current margin of exposure (MOE) methods, we note that while the first method is effective in highly polluted areas, it is more appropriate to use the MOE calculation method in non-polluted areas. This method allows for the identification of potential public health risks caused by exposure to toxic elements, even at minimal levels, based on regularly updated toxicological data, particularly health-based guideline values. Overall, the study findings highlight the potential health risks associated with consuming locally grown produce in contaminated areas, indicating a need for continuous monitoring and effective risk management strategies. The study emphasizes the importance of addressing environmental pollution in agricultural areas to protect public health and ensure food safety. As the impacts of mining extend beyond economic benefits, this research shows the necessity of mitigating exposure to harmful elements in the food chain. В рамках исследования выявлены риски для здоровья, обусловленные воздействием токсичных (Pb, Cd, As, Hg) и потенциально токсичных (Mo, Cu) элементов при употреблении в пищу овощей (картофеля, моркови, фасоли, укропа, тыквы), выращенных в горнодобывающих районах. Был применен метод расчета предела воздействия (MOE), результаты сравнены с ранее полученными значениями целевого коэффициента опасности (THQ). За основу были приняты обновляемые токсикологические данные, в частности ориентировочные значения, установленные нормативами по охране здоровья. В случае употребления всех исследуемых овощей зафиксированы высокие значения риска (MOE<10) от воздействия Pb, Mo и Cu, а при употреблении картофеля и укропа – также As. Сравнение результатов двух методов показывает, что THQ эффективен на территориях с высоким уровнем загрязнения, в то время как в незагрязненных районах целесообразнее использовать метод MOE. Последний позволяет выявить потенциальные риски для здоровья даже при воздействии минимального количества токсичных элементов.
Keywords: Սննդագիտություն և տեխնոլոգիա